1975
DOI: 10.1126/science.1114319
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Toxicity from Combustion Products of a Fire-Retarded Polyurethane Foam

Abstract: The products from nonflaming combustion of wood and a trimethylol-propane-based rigid-urethane foam that was not fire-retarded produced elevated carboxyhemoglobin levels but no abnormal neurological effects. However, when this type of foam contained a reactive phosphate fire retardant, the combustion products caused grand mal seizures and death in rats. The toxic combustion product responsible for the seizures has been identified as 4-ethyl-1-phospha-2,6,7-trioxabicyclo(2.2.2.)octane-1-oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(45 citation statements)
references
References 3 publications
0
44
0
Order By: Relevance
“…Solid-state structure of 1 (PLATON [12] plot). Characteristic bond lengths [] and angles [8]: P ± O1 1.601(1), P ± O2 1.587(1), P ± O3 1.463(2), P ± C14 1.782(2), O1 ± C1 1.414(2), O2 ± C13 1.396(2), C6 ± C7 1.515(3), C7 ± C8 1.508(3), C ar ± C ar 1.386 (av distance); O1-P-O2 106.0(1), O1-P-O3 113.8(1), O2-P-O3 114.7(1), O2-P-C14 100.1(1), O1-P-C14 101.5(1), O3-P-C14 118.9(1), P-O1-C1 120.5(1), P-O2-C13 129.9(1), C6-C7-C8 111.0(1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid-state structure of 1 (PLATON [12] plot). Characteristic bond lengths [] and angles [8]: P ± O1 1.601(1), P ± O2 1.587(1), P ± O3 1.463(2), P ± C14 1.782(2), O1 ± C1 1.414(2), O2 ± C13 1.396(2), C6 ± C7 1.515(3), C7 ± C8 1.508(3), C ar ± C ar 1.386 (av distance); O1-P-O2 106.0(1), O1-P-O3 113.8(1), O2-P-O3 114.7(1), O2-P-C14 100.1(1), O1-P-C14 101.5(1), O3-P-C14 118.9(1), P-O1-C1 120.5(1), P-O2-C13 129.9(1), C6-C7-C8 111.0(1).…”
Section: Resultsmentioning
confidence: 99%
“…[7] Highly toxic combustion products of fire retardants based on organophosphates were first observed by Petajan et al, who found that 4-ethyl-1-phospha-2,6,7-trioxybicyclo-[2.2.2]octan-1-oxide is formed during the combustion of a phosphorus fire-retarded polyurethane foam. [8] [ In a study on epoxy resins containing covalently fixed phosphonate substructures, we investigated the toxicological potential of these new fire retardants and of their combustion products for the first time. Herein we report the isolation, characterization and toxicological evaluation of the major volatile organophosphorus compounds formed during the combustion of these new polymeric materials.…”
Section: Introductionmentioning
confidence: 99%
“…The biological testing method, using Wistar rats, has been fully described in previous papers39 and can be (2) mobile furnace, (3) driving system of furnace; (4) Ni-NiCr thermocouple; (5) ventilator; ( 6 ) throttle valve; (7) precision flow-meter; (8) reduction tube; (9) T-junction for the addition of dilution air; (10) quartz crucible as sample holder; (11) distribution chamber; (1 2) wash bottles.…”
Section: Methodsmentioning
confidence: 99%
“…However, as noted earlier, an unusual toxic effect was observed when animals were exposed to the combustion products from a laboratory formulated rigid polyurethane foam based on a propoxylated trimethylolpropane (MW 340) and polymethylene polyphenyl isocyanate containing the reactive fire retardant 0, 0-diethyl-N, N-bis (2-hydroxyethy1)-aminomethyl phosphonate (4-8 ~t % ) .~~*~~9~~ When this fire retarded foam was irradiated by a radiant heat flux of 5 W cm-2 in the NBS smoke chamber, the non-flaming thermal degradation products produced grand ma1 seizures and death in rats following a 20-min exposure. 33 The grand ma1 seizures occurred in the rats during the first hour following the exposure to smoke from this particular fire-retarded polyurethane foam. Additional physiological changes included alterations in the respiratory response to smoke irritants, high amplitude spike discharges in the EEG and blood COHb levels of approximately 6%.…”
Section: Miscellaneous Studies University Of Michigan Testsmentioning
confidence: 99%